A Systematic Literature Review (SLR): Penerapan Konseling Teknik Art Therapy untuk Mereduksi Stress Akademik Mahasiswa - Mulyaningtyas (Universitas Palangka Raya, 2023)
Art therapy counseling is counseling involving artistic processes, such as drawing as a symbolic form of a therapeutic relationship to help the therapist gain self-understanding and the pressures experienced by clients. Art therapy counseling helps students resolve conflicts, improves interpersonal skills, manages problematic behavior, reduces stress. The purpose of this research is to find out techniques in art therapy counseling that can be used to reduce student academic stress. This research is a systematic literature review using the Research Question method. It is hoped that after knowing art therapy counseling techniques, counselors are able to apply them in the counseling process to help reduce student academic stress.